Cost-Benefit Rules for Public Good Provision with Distortionary Taxation - Jeremy Edwards (Center for Economic Studies and ifo Institute (CESifo), 2001)
The paper shows that a comparison of the appropriately-weighted sum of households' marginal willingness to pay for a public good with the net effect of the increased supply of the public good on shadow, as distinct from actual, government revenue is a generally valid rule for public good provision. This rule does not depend on any assumption that existing policy is optimal. The practical problems in measuring the true social cost of additional public good provision involve the need to estimate shadow prices of non-traded goods and goods which are not traded at given world prices The marginal cost of public funds is not required in order to measure the social cost of public good provision.
Keywords: 330